Developing Marketing Innovation for Sustainability of Community Businesses, Kap Choeng District, Surin Province - Nithichaianan , Navarat; Wuttipiyapong, Rabeab; Nithisiriwaritkun , Wimolkran; Pattanachatchai , Napapan; Nanua , Saranya (Journal of Human and Society, Sisaket Rajabhat University, 2023)
This research aimed to investigate the impact of marketing innovations on the sustainability of community businesses in Kap Choeng District, Surin Province. A mixed-method research approach was employed, using surveys as a quantitative research tool with a sample size of 180 participants and qualitative research methods, including interviews and group discussions with 30 individuals. The study found that marketing innovations in community businesses and overall business sustainability are high, with a strong focus on customer-centricity. Marketing innovations in community businesses that influence sustainability are also at a high level, particularly in terms of unique value propositions, niche marketing, and inclusive marketing communication, all significantly impacting community business sustainability at a statistically significant level of 0.05. Based on the research findings, it is recommended to develop marketing innovations to ensure the sustainability of community businesses. Using online social media platforms that align with the current era and employ diverse and continuous communication strategies is recommended. Creating a distinct brand that enhances product memorability and value is also crucial. Product diversification should be encouraged to provide distinctiveness to the products, and product design should align with the target audience’s characteristics. Additionally, diverse distribution channels should be established, adopting new-age marketing approaches for broad customer reach. This approach will generate trade opportunities, expand customer bases, and increase revenue, ultimately leading to the sustainability of community businesses.